Current status of malaria parasite among blood donors in Port Harcourt, Rivers State, Nigeria - AE Abah; O Joe-Cliff (Journal of Applied Sciences and Environmental Management)
This study was carried out to determine the prevalence of malaria parasite among blood donors at the  Police Clinic Port Harcourt, Rivers State, Nigeria. The standard parasitological techniques using both thick and thin blood films from the donors for the detection of malaria parasite was followed. Venous blood was collected from 200 blood donors and films were made on clean greese-free glass slide and stained with 10%Giemsa stains and viewed under the microscope using the oil immersion objective. Of the 200 samples examined, 56 (28.00%) were positive with Plasmodium falciparium. The highest prevalence among the males 53(26.50%) and between the ages 21-30years and only 3 (1.50%) of females were positive. Donors having the blood group O were more infected (60.70%) than the other blood groups and the lowest was blood group AB (5.40%). This result shows that there is a relatively high prevalence of malaria parasite among the blood donors in Port Harcourt, Nigeria. It is, therefore, recommended that malaria parasite screening test be included among other blood screening tests before any transfusion to avert the deleterious effects of malaria on recipients. © JASEM